PERAN HUMAS JOBHUN DALAM MEMPERTAHANKAN EKSISTENSI DI TENGAH PERSAINGAN PADA MASA PANDEMI - Nur Auwaliyah Amin; Marisa Novita Angelin Dalima; Nanda Rachma Dewi; Syafira Aurell Irma Putri; Silvia Ika Aristin; Dyva Claretta; Dian Hutami Rahmawati (DAS Institute, 2022)
This pandemic has brought changes to many businesses, one of which is how start up business grows in number. Jobhun which was originally the only startup platform in the field of skills development in Surabaya, now has many competitors. In addition, Jobhun's existence will also be threatened if Jobhun is not able to face startup competition in this pandemic era. Hence, companies need a public relations team to deal with the very tight competition between startup companies. How a company deals with some issues reflects the quality of their Public Relations. With this background, the purpose of this research is to investigate the strategy performed by Jobhun Public Relations in facing competition and maintaining existence during the covid19 pandemic. The type of this research is qualitative research with its methodology to collect the data is in-depth interview. The participant of this study is Jobhun's public relations and marketing team. The result of this study shows that to face Public Relations competition, not only they conduct online skills training classes, but they also collaborate with Mentors, company HRD, student organizations, partnerships and also competitors. In this collaboration, they create content which is then consulted to Jobhun’s marketing team. In order to maintain its existence, Jobhun continues to innovate and open internships. The conclusion of this research shows that the strategy they use is effective which is indicated by the increase in their income and followers of social media.